The influence of rivaroxaban compared to vitamin K antagonist treatment upon development of cardiovascular calcification the IRIVASC-trial. (3rd October 2022) - Stoehr, R; Marx, N; Schuh, A; Brandenburg, V
Abstract: : Vitamin K antagonists (VKA) such as warfarin or phenprocoumon are the mainstay of therapy for patients with several specific indications for long-term oral anticoagulant therapy (OAT). Due to interferences with Matrix-Gla protein, an important vitamin K-dependent local calcification inhibitor in cardiovascular structures, VKAs are theoretically linked to the development of increased cardiovascular calcification (CVC). The IRIVASC trial was a multi-center, prospective, controlled, open, randomized, interventional clinical trial and included 192 patients with atrial fibrillation or pulmonary embolism and an indication for oral anticoagulation >12 months. In short, patients with an indication for OAT were randomized to receive either Rivaroxaban (n=96) or VKA (n=96) and followed up over 12 months. MultiSlice CT (MSCT) was performed at baseline and after 12-month follow up. The primary endpoint of the study was the progression of coronary artery and aortic valve (AV) calcification, as determined by MSCT (volume score). Baseline demographic and laboratory values were comparable between the VKA and the Rivaroxaban groups (median age 72 vs 68, 73.6 vs 69.9 male). The main indication for anticoagulation was AF (95.4% vs 96.6%) After 12-month follow-up complete data sets were available for 164 patients (86%) for coronary calcification and 67 patients for valvular calcification (per protocol analysis). Overall, we found no differences in the primary endpoints. Development of coronary artery calcification was similar within the 2 groups as evidenced by similar developments of the coronary agatston score (804.8±1062.3 vs 946.7±1024.4, p=0.38), the coronary volume score (571.9±855.6 ml vs 791.7±820.1 ml, p=0.359) and the coronary mass score (143.2±195.9 mg vs. 172.2±190.8 mg, p=0.335) after 12 month. Similarly, there was no difference in the development of aortic valve calcification (AV) (AV Agatston score 441.6±711.9 vs. 352.6±751.2, p=0.621. AV volume score 388.2±589.0 ml vs 354.3±654.3, ml p=0.824 and AV Mass Score 75.7±135.1 mg vs 60.2±122.9, p=0.626 mg) (Table 1). To our knowledge this is the first multicenter prospective, randomized trial to ever investigate the effects of VKA vs rivaroxaban treatment regarding the development of coronary and valvular calcification. Our findings are clinically relevant as VKA will remain the mainstay of treatment for several conditions including mechanical valve replacement or antiphospholipid syndrome and hence include patients at cardiovascular risk. Our data point towards a comparable risk of overt CVC progression as detectable by CT-scans in patients irrespective of VKA or NOAK treatment. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BAYER GmBH